The Effects of Inflationon Economic Growth : Lessons From Latin America - De Gregorio, Jose (IMF Working Papers; Working Paper, 1991)
This paper investigates the relationship between inflation and long-run growth. It presents an endogenous growth model that illustrates the channels through which inflation affects growth. The model highlights the effects of inflation on the productivity of capital and the rate of capital accumulation. The reduction in growth is caused by a diversion of resources away from activities that lead to faster rates of growth toward activities associated with reducing the costs of inflation. The negative association between inflation and growth is assessed empirically for a sample group of Latin American countries.